Telogen effluvium as a symptom of “Long Covid” in patients pre-infected with SARS-CoV-2: an integrative literature review (Research, Society and Development, 2022)
COVID-19 is a relatively new disease that presents a broad spectrum of clinical manifestations, among them is telogen effluvium, a condition that promotes diffuse hair loss in the patient, usually after the end of the infection. This article is a narrative literature review that seeks to understand the pathogenesis of telogen effluvium, as well as the impacts of this symptom on patients' lives. For this, a search was carried out in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO Information Services in order to collect the most current information on the topic. Thus, it was noted that telogen effluvium was a complex symptom, as it probably involves more than one mechanism in its pathogenesis. In addition, the study is justified by the effect it has on the self-esteem and self-image of patients who, seeing their hair fall out, have their emotional stress increased. With regard to treatment, correction of the triggering factor, combined with the implementation of a protein-rich diet, proved to be effective in stopping hair loss.